Specificity of curvilinear sprint performance in youth female soccer players: comparison with linear sprint and relationship with vertical jumps - Sašek, M.; Smajla, D.; Bratina, K.; Spudic, D. (International Journal of Performance Analysis in Sport, 2026)
Differences between left and right curvilinear (CSL and CSR) and linear sprinting (LS) and their relationship to vertical jump performance in youth female soccer players were investigated. Twenty-four players completed 30 m LS, CSL and CSR together with vertical jumps (single-leg and bilateral countermovement jump, squat jump and drop jump). Sprint times (10, 20, 30 m), peak speed (Speak), peak acceleration (Apeak) and acceleration-speed profiles including maximal theoretical speed (S0), maximal theoretical acceleration (A0) and acceleration speed slope (ASslope) were calculated. The influence of sprint type on the variables was analysed using ANOVA, while the Pearson correlation coefficient was used to investigate the relationship between jump height and sprint performance. Sprint type had a significant effect on most variables (p <= 0.003, Eta2 >=0.14), except Apeak. LS showed higher Speak, maximal theoretical speed (S0), 20 m and 30 m split times compared to CSL and CSR. Single-leg countermovement jumps correlated strongly with Speak and S0 (r >= 0.46). Furthermore, LS and CS performance variables were trivially to strongly correlated (r = 0.04-0.78). The results highlight the specific demands of CS compared to LS and emphasise the role of unilateral lower-limb power for CS performance in female soccer players.